2002
DOI: 10.1007/s00228-002-0471-4
|View full text |Cite
|
Sign up to set email alerts
|

A Swedish case-control network for studies of drug-induced morbidity – acute pancreatitis

Abstract: In addition to cholelithiasis, smoking and heavy alcohol use, drugs may be an important risk factor for acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 38 publications
3
63
1
4
Order By: Relevance
“…Talamini et al [3] described an association between smoking and acute pancreatitis in a study where smoking habits among patients with acute alcoholic pancreatitis were compared with smoking habits among control individuals who were randomly selected from the background population. Blomgren et al [5] found that smoking was significantly associated with acute pancreatitis in a study in which patients hospitalized with an increased amylase level were compared to controls randomly chosen from a population register. These studies are both retrospective case-control studies which may affect the validity of exposure assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Talamini et al [3] described an association between smoking and acute pancreatitis in a study where smoking habits among patients with acute alcoholic pancreatitis were compared with smoking habits among control individuals who were randomly selected from the background population. Blomgren et al [5] found that smoking was significantly associated with acute pancreatitis in a study in which patients hospitalized with an increased amylase level were compared to controls randomly chosen from a population register. These studies are both retrospective case-control studies which may affect the validity of exposure assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Several other risk factors have been proposed, including different drugs, toxins and metabolic and endocrine disorders [2] . Some previous studies have indicated that there may be an increased risk for acute pancreatitis among smokers [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La PA dans les MICI peut faire partie des manifestations extra-intestinales ou être secondaire aussi bien à l'AZA qu'a son métabolite la 6-MP ou à un traitement par dérivéss alicylés( m é salazine ou sulfasalazine) [1][2][3][4][5]. Le traitement immunosuppresseur par l'AZA ou la 6-MP au ne capacité certaine d'induire une PA ; cependant, la toxicité pancréatique est rare, estimée à 1,4 % [ 1,6,7].…”
Section: Discussionunclassified
“…Le traitement immunosuppresseur par l'AZA ou la 6-MP au ne capacité certaine d'induire une PA ; cependant, la toxicité pancréatique est rare, estimée à 1,4 % [ 1,6,7]. Les facteurs de risque rapportés dans la littérature sont la maladie de Crohn où le risque est multiplié par 4a lors que dans la RCH, le risque est multiplié par deux, le sexef é minin et l'association aux aminosalycilés [ 8,9].Ces pancréatites surviennent généralement au cours du premier mois du traitement et sont généralement bénignes [4,5,8] comme c'est le cas chez notre patiente. Cliniquement, les symptômesd el aP As ont parfois difficiles à différencier de ceux causésp ar l'activité des MICI ou de leurs complications.…”
Section: Discussionunclassified